Coping, parental stress and quality of life of primary caregivers of people with ASD - Montserrat Durán; Manuel García-Fernández; Juan Carlos Fernández; Beatriz Sanjurjo (Revista de Estudios e Investigación en Psicología y Educación, 2016)
The aim of this study was to analyze the quality of life of primary caregivers of people with ASD. 50 caregivers of people with ASD aged between 2 and 35 years participated in this study. Besides the quality of life, coping strategies and parental stress were also evaluated. The results showed that (1) parental stress, coping strategies and quality of life were not significantly associated with the developmental stage of the person with ASD; (2) the quality of life in the psychological, social and environmental domains is worse in caregivers with levels of parental stress clinically significant; and (3) the quality of life in the psychological domain is better among those using more adaptive coping strategies, such as social support or positive reappraisal. On the contrary, the use of coping strategies such as aggressive reaction, avoidance or emotional difficulties are associated with a poorer quality of life in the psychological, social and environmental domains Keywords: quality of life, parental stress, coping, ASD.